2012
DOI: 10.3233/wor-2012-0908-5652
|View full text |Cite
|
Sign up to set email alerts
|

The influence of an abdominal support for a dental stool in the distributions and electrical activity of the longissimus and the superior trapezius muscle in dentists

Abstract: This study evaluated the influence an abdominal support attached to a traditional stool, of those used by dentists, has on the body's distribution of the electrical activity of the superior trapezius and the longissimus thoracic muscles of dental students during the execution of a clinical procedure. The results showed no significant difference in the body's distribution in the seat and backrest, but did reveal there was a weight discharge of 3.1±1.9% of dentist's body weight in the abdominal support. The 9 o'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
1
1
0
1
Order By: Relevance
“…The results indicated an intermediate to high score for ergonomic risk in the group using the conventional seat, which is consistent with other studies [36,39]. Over the last decade, research has been intensified, designing the effects of different seats on the clinical practice of dentists and dental students [11][12][13][40][41][42]. Among such studies, three have investigated the ergonomically modified stool [40][41][42] and three have investigated the saddle seat [11][12][13].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The results indicated an intermediate to high score for ergonomic risk in the group using the conventional seat, which is consistent with other studies [36,39]. Over the last decade, research has been intensified, designing the effects of different seats on the clinical practice of dentists and dental students [11][12][13][40][41][42]. Among such studies, three have investigated the ergonomically modified stool [40][41][42] and three have investigated the saddle seat [11][12][13].…”
Section: Discussionsupporting
confidence: 84%
“…Over the last decade, research has been intensified, designing the effects of different seats on the clinical practice of dentists and dental students [11][12][13][40][41][42]. Among such studies, three have investigated the ergonomically modified stool [40][41][42] and three have investigated the saddle seat [11][12][13]. All studies showed an improvement in the experimental group when compared to the control group, especially for presenting a lumbar lordosis seated posture [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…En relación a las intervenciones ergonómicas implementadas, y su impacto sobre la sobrecarga muscular, se concentran, por un lado, en cambios en el equipamiento y en el mobiliario, desarrollando por ejemplo, estudios comparativos con distintos tipos de silla o taburete para el ejercicio de la profesión (14,(16)(17)(18)(19), la comparación entre instru-mentos alámbricos e inalámbricos (20), el uso de instrumental manual con diseños ergonómicos (21) o de instrumental mecanizado (ultrasónico) (22).…”
Section: Discussionunclassified